2015
DOI: 10.1002/navi.74
|View full text |Cite
|
Sign up to set email alerts
|

Jamming Detection in GNSS Receivers: Performance Evaluation of Field Trials

Abstract: ABSTRACT:We evaluate the detection performance of several commercial interference detectors and of a detector that uses the automatic gain control (AGC) level as a test statistic. The evaluations are based on actual measurements of GPS signals and different types of jamming signals, and were performed at the Vidsel test range in northern Sweden. The AGC detector and the Chronos CTL-3500 were shown to work well for all types of jamming signals. The J-alert was able to detect a wideband (20 MHz) signal but not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 10 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…C/N 0 is a common measurement of the signal quality from a GPS satellite at the receiver. Although C/N 0 can be used to detect the interference, it cannot distinguish between the increased jamming signal power and the decreased GPS signal power so that it might lead to false alarms [13]. For example, the C/N 0 estimates would decrease during an RFI event or when the GPS signal is weakened due to blockage by a building or other objects.…”
Section: B Energy Detector Measurementmentioning
confidence: 98%
“…C/N 0 is a common measurement of the signal quality from a GPS satellite at the receiver. Although C/N 0 can be used to detect the interference, it cannot distinguish between the increased jamming signal power and the decreased GPS signal power so that it might lead to false alarms [13]. For example, the C/N 0 estimates would decrease during an RFI event or when the GPS signal is weakened due to blockage by a building or other objects.…”
Section: B Energy Detector Measurementmentioning
confidence: 98%
“…In particular, a Bernoulli decision scheme was designed. In [34] and [55], detection approaches based on individual C=N 0 were also considered and it was confirmed that "C=N 0 -based detectors could work well in a static scenario, but are not suitable in a dynamic scenario, since they cannot distinguish between decreased GPS signal strength and an increased interference level." This is the so-called C=N 0 ambiguity problem: the estimated C=N 0 can decrease either because the signal power C is attenuated or because of the additional noise power introduced by jamming.…”
Section: Postcorrelation Domain Detectionmentioning
confidence: 99%
“…Thus, in the presence of jamming, C=N 0 estimated by the receiver can be significantly reduced. For this reason, C=N 0 has been adopted by several researchers [32]- [34], [53], [55], [56] as an indicator for jamming detection.…”
Section: Postcorrelation Domain Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a fully heuristic model mimicking (17) is considered. In particular, the excess kurtosis is modeled as 19) where in this case, K 0 and˛have no physical meaning. Although the excess kurtosis is heavily affected by saturation effects, model (19) seems to capture the general behavior of this metric.…”
Section: Sdr-related Metricsmentioning
confidence: 99%